A SEGMENT ANALYSIS OF PREMIUM CONTRIBUTIONS WITHIN MULTI-LINE INSURERS (DEVELOPED VS. DEVELOPING COUNTRIES) - Chitate, Alfonce (2018)
We take motivation from the absence of previous literature into the determinants on premium contributions made by different segment lines. We investigate on a global level, looking into seventy-seven multi-line insurance companies in thirty-one countries. This paper seeks to determine if “Life and Health” insurance products contribute differently towards gross written premium in developed countries versus developing countries. It explores how this difference is attributable to socio-economic factors that are a part of determining the economic classification. A Fixed effects model is used on the multi-line insurers data to determine the effects on Life & Health insurance products contribution to gross written premium. While eleven explanatory variables are statistically significant the other eighteen are not. This study finds that socio-economic factors explain a significant amount of the variance found in the dependent variable. The findings provide information on trends that should be used to inform strategic decision making for multi-line practitioners and policy makers.